1997
DOI: 10.1124/mol.51.6.951
|View full text |Cite
|
Sign up to set email alerts
|

2-Methoxyestradiol, an Endogenous Estrogen Metabolite, Induces Apoptosis in Endothelial Cells and Inhibits Angiogenesis: Possible Role for Stress-Activated Protein Kinase Signaling Pathway and Fas Expression

Abstract: 2-Methoxyestradiol (2-ME) is an endogenous metabolite of estradiol-17beta and the oral contraceptive agent 17-ethylestradiol. 2-ME was recently reported to inhibit endothelial cell proliferation. The current study was undertaken to explore the mechanism of 2-ME effects on endothelial cells, especially whether 2-ME induces apoptosis, a prime mechanism in tissue remodeling and angiogenesis. Cultured bovine pulmonary artery endothelial cells (BPAEC) exposed to 2-ME showed morphological (including ultrastructural)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
130
0
2

Year Published

2003
2003
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 174 publications
(138 citation statements)
references
References 38 publications
6
130
0
2
Order By: Relevance
“…2-MeOE2 induces apoptosis and inhibits angiogenesis in many tumour models, indicating that this compound has considerable potential as an antitumour agent. [1][2][3][4][5][6][7][8][9][10][11] Previous studies from our group have shown that these sulphamoylated derivatives induce an irreversible G2-M arrest and inhibit proliferation of not only androgen receptor 1ve/2ve prostrate, ovarian, and breast cancer cells, but also cells resistant to conventional chemotherapeutic agents, such as adriamycin and cisplatin. 26,27 In all these studies, sulphamoylated derivatives of 2-MeOE2, 2-MeOE2-MATE, and 2-MeOE2bisMATE are significantly more potent at inducing cell cycle arrest and apoptosis than 2-MeOE2.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…2-MeOE2 induces apoptosis and inhibits angiogenesis in many tumour models, indicating that this compound has considerable potential as an antitumour agent. [1][2][3][4][5][6][7][8][9][10][11] Previous studies from our group have shown that these sulphamoylated derivatives induce an irreversible G2-M arrest and inhibit proliferation of not only androgen receptor 1ve/2ve prostrate, ovarian, and breast cancer cells, but also cells resistant to conventional chemotherapeutic agents, such as adriamycin and cisplatin. 26,27 In all these studies, sulphamoylated derivatives of 2-MeOE2, 2-MeOE2-MATE, and 2-MeOE2bisMATE are significantly more potent at inducing cell cycle arrest and apoptosis than 2-MeOE2.…”
Section: Discussionmentioning
confidence: 99%
“…1-9 2-MeOE2 also inhibited the proliferation, migration, and invasion of capillary endothelial cells and angiogenesis in several in vitro and in vivo tumour models. 2,8,10 In addition, 2-MeOE2 inhibited tumour growth in murine xenograft models of MDA-MB-235 cells and H460 non-small cell lung carcinoma. 8,11 In a Gy/T-15 transgenic murine model of androgen-independent prostate cancer, 2-MeOE2 inhibited the progression of the tumour without toxic side effects.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This observation might be important in the light of the inherent resistance of melanomas to drug-induced apoptosis. 38,39 Reports on the effects of 2ME 2 on the expression of apoptosis regulating proteins (e.g., p53 and Bcl-2) 16,24,26,29,36,40 suggest that 2ME 2 may have a potential to overcome apoptosis resistance of melanoma cells.…”
Section: Discussionmentioning
confidence: 99%
“…Angiogenesis is a closely controlled biological process, which takes place during fetal development of blood vessels and wound healing (Folkman & Shing, 1992;Yue et al, 1997). It is also an essential requirement to enable tumor growth (Yue et al, 1997;Hall et al, 2013).…”
Section: Introductionmentioning
confidence: 99%